PESANTREN DAN PEMBERDAYAAN EKONOMI MASYARAKAT (STUDI PON-PES BAITURRAHMAN PARAU SORAT) - Erpiana Siregar (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
The purpose of this study was to determine how the empowerment activities of the potential of Islamic boarding schools in making the Baiturrahman Islamic boarding school in Parau Sorat village independent were for students, the elderly, and the surrounding community. This study collected data by interviewing the head of the foundation, teachers, the elderly, students, and the community around the Islamic boarding school regarding how economic empowerment was carried out by the Islamic boarding school. Then the results of the interviews were presented and conclusions were drawn related to the research theme. The results of the study showed that economic empowerment at the Baiturrahman Islamic boarding school was carried out by empowering students, the elderly, and the community around the Islamic boarding school. Student empowerment activities were carried out through training in agribusiness, animal husbandry, fisheries, calligraphy, and rice groups. Economic empowerment carried out for the elderly who live at the Baiturrahman Islamic boarding school is by providing land to be cultivated. While the surrounding community with oil palm plantation partnerships.